Muslim Brotherhood: the sudden transition from the steering wheel to the anchor (Journal of Oriental Studies, 2016)
this article examines the background and reasons-consequences of the current political instability in egypt. there is a trying to find answers to questions about who needed the victory of the Muslim brotherhood after the arab spring and what the implications of their removal from power.
Keywords: Muslim brotherhood; arab spring; revolution in egypt; Us’s strategy